Establishing criteria for evaluating the Portuguese geological heritage - Fonseca, H. (2005)
The present work aims to test methodological approaches in the evaluation of the geological heritage. Procedures normally used in the assessment of biological values will be adapted for geosites evaluation. The Sintra-Cascais Natural Park, a protected area located in the Lisbon region, will be used as a case study.